2021
DOI: 10.3390/microorganisms9040870
|View full text |Cite
|
Sign up to set email alerts
|

Gluconacetobacter diazotrophicus Pal5 Enhances Plant Robustness Status under the Combination of Moderate Drought and Low Nitrogen Stress in Zea mays L.

Abstract: Plant growth promoting endophytic bacteria, which can fix nitrogen, plays a vital role in plant growth promotion. Previous authors have evaluated the effect of Gluconacetobacter diazotrophicus Pal5 inoculation on plants subjected to different sources of abiotic stress on an individual basis. The present study aimed to appraise the effect of G. diazotrophicus inoculation on the amelioration of the individual and combined effects of drought and nitrogen stress in maize plants (Zea mays L.). A pot experiment was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…This might be due to the presence of Cis elements [16]. Similarly, GdPAL5 is also reported to be an auxin producer which activates plant defense mechanisms during the abiotic stress [83]. Different gene family members usually display abundance disparities in different tissues or under distinct stresses [84].…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the presence of Cis elements [16]. Similarly, GdPAL5 is also reported to be an auxin producer which activates plant defense mechanisms during the abiotic stress [83]. Different gene family members usually display abundance disparities in different tissues or under distinct stresses [84].…”
Section: Discussionmentioning
confidence: 99%
“…The extent of plant adaptation to drought stress is often measured by increases in plant biomass (Dastogeer, Chakraborty, et al, 2020a; Munns, 2002; Tufail, Touceda‐González, et al, 2021b). Indeed, our meta‐analysis revealed that EB and EF inoculation increased biomass output, which is consistent with prior findings (Dastogeer, Chakraborty, et al, 2020a; Dubey et al, 2021; Rho et al, 2018; Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The extent of plant adaptation to drought stress is often measured by increases in plant biomass (Dastogeer, Chakraborty, et al, 2020a;Munns, 2002;Tufail, Touceda-González, et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all plant-associated bacteria, endophytes show to relive the impacts of salt stress in plants by inducing osmotic adjustment, detoxification, modulation of phytohormones, and acquisition of nutrients [ 17 , 18 , 19 ]. Endophytic bacteria with 1-aminocylopropane−1-carboxylate (ACC) deaminase and indole−3-acetic acid (IAA) production, nitrogen fixation, phosphate solubilization, and siderophore production traits have shown to promote the osmotic or ionic adaptation of host plants [ 20 , 21 , 22 , 23 , 24 ]. However, the exact endophytic bacterial-mediated mechanisms underlying salt stress alleviation remain largely unknown [ 25 ].…”
Section: Introductionmentioning
confidence: 99%